Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.14742/ajet.2526
|View full text |Cite
|
Sign up to set email alerts
|

Re-designing university courses to support collaborative knowledge creation practices

Abstract: <p>Higher education institutions should not only aim to educate academic experts who master their own fields, but also give their students generic skills important in contemporary society. New teaching methods are required to support the development of such skills. The study examined how a group of voluntary university lecturers re-designed their courses by applying theory-based pedagogical design principles emphasising object-oriented, collaborative knowledge creation supported by digital technology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…The statements were not originally developed for research purposes, but the organizers wanted to be able to compare the results to the feedback from previous years. The two open-ended questions were adopted from previous studies investigating students' self-reported experiences in university courses (e.g., Lakkala, Toom, Ilomäki, & Muukkonen, 2015).…”
Section: Data Collectionmentioning
confidence: 99%
“…The statements were not originally developed for research purposes, but the organizers wanted to be able to compare the results to the feedback from previous years. The two open-ended questions were adopted from previous studies investigating students' self-reported experiences in university courses (e.g., Lakkala, Toom, Ilomäki, & Muukkonen, 2015).…”
Section: Data Collectionmentioning
confidence: 99%
“…Across disciplines there has also been a call to ensure that students learn generic competencies including critical and analytical thinking (e.g. Strijbos et al, ) as well as knowledge work competencies that describe utilization of collective efforts facing open‐ended problems, the rich use of modern technologies, encounters with real‐world complexity through work life contacts and developing specific tasks for some relevant use (Lakkala et al, ). In addition to communication skills, other nontechnical professional competencies, such as empathy and self‐efficacy, have also been supported by evidence to be important elements of professionalism (Mueller, ; Cake et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The first implementations are often something between the previous and the new targeted practices, as noticed when revising higher education courses through the TLA [37]. Similarly, in the investigated school, the second implementations were improved versions of the first ones, just as were the teachers' new ideas for the future.…”
Section: Discussionmentioning
confidence: 98%